2012
DOI: 10.1111/j.1530-9134.2012.00346.x
|View full text |Cite
|
Sign up to set email alerts
|

Firm Productivity and the Foreign‐Market Entry Decision

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 33 publications
2
47
1
Order By: Relevance
“…A few studies on cross-border acquisitions in different institutional settings have analyzed the impact of firm-specific characteristics and their affect on success of overseas negotiations (e.g., Forssbaeck & Oxelheim, 2008;Raff, Ryan, & Stähler, 2012;Zhu, Jog, & Otchere, 2011). First and foremost, Gonzalez, Vasconcellos, Kish, and Kramer (1997) found that firms acquiring US-based firms have better liquidity ratio, while targets have low price-to-earnings ratio.…”
Section: Firm-and Industry-specific Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…A few studies on cross-border acquisitions in different institutional settings have analyzed the impact of firm-specific characteristics and their affect on success of overseas negotiations (e.g., Forssbaeck & Oxelheim, 2008;Raff, Ryan, & Stähler, 2012;Zhu, Jog, & Otchere, 2011). First and foremost, Gonzalez, Vasconcellos, Kish, and Kramer (1997) found that firms acquiring US-based firms have better liquidity ratio, while targets have low price-to-earnings ratio.…”
Section: Firm-and Industry-specific Factorsmentioning
confidence: 99%
“…In particular, Raff et al (2012) analyzed the direct international investments in 21 developed countries made by Japanese firms between 1985 and 2000. They indicated that firms with greater levels of productivity likely to chose FDI (greenfield) than export strategy (acquisition).…”
Section: Firm-and Industry-specific Factorsmentioning
confidence: 99%
“…Since we have access to detailed firm-level information, we can control for a number of additional firm characteristics, such as total assets (excluding land), total factor productivity (TFP), previous investment experience, market value, and cash flow, all known to be associated with FDI (see, for instance, Raff et al, 2012). We can also control for whether a firm and its main bank are in the same keiretsu.…”
Section: Marketmentioning
confidence: 99%
“…Our results would remain qualitatively the same, if the investor had to choose simultaneously between the acquisition of a local firm and greenfield investment. 8 Empirical evidence suggests that such decisions are indeed made simultaneously, especially given a long lead time that greenfield investments generally require; see, for example, Raff et al (2012).…”
Section: The Modelmentioning
confidence: 99%